2014
DOI: 10.1016/j.psyneuen.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic responses to early adversity: Implications for affective problems and autism spectrum disorder

Abstract: During gestation, development proceeds at a pace that is unmatched by any other stage of the lifecycle. For these reason the human fetus is particularly susceptible not only to organizing influences, but also to pathogenic disorganizing influences. Growing evidence suggests that exposure to prenatal adversity leads to neurological changes that underlie lifetime risks for mental illness. Beginning early in gestation, males and females show differential developmental trajectories and responses to stress. It is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 122 publications
(153 reference statements)
8
105
0
3
Order By: Relevance
“…These neurodevelopmental disorders exhibit a strong sex bias, where boys are more likely to develop ASD, ADHD, and earlier-onset schizophrenia (Baio, 2012;Bloom et al, 2011;Froehlich et al, 2007;Zhang et al, 2012). Consistent with the male predominance of these disorders, recent epidemiological and preclinical studies suggest that males are uniquely vulnerable to prenatal adversity (Clifton, 2010;Davis and Pfaff, 2014). Although studies have revealed sex-specific changes in the developing brain (Bale, 2011;Matthews, 2005, 2008;Kapoor et al, 2009;Weinstock, 2011), the specific mechanisms by which perturbations in the maternal environment promote sex-biased fetal reprogramming remain unclear.…”
Section: Introductionmentioning
confidence: 94%
“…These neurodevelopmental disorders exhibit a strong sex bias, where boys are more likely to develop ASD, ADHD, and earlier-onset schizophrenia (Baio, 2012;Bloom et al, 2011;Froehlich et al, 2007;Zhang et al, 2012). Consistent with the male predominance of these disorders, recent epidemiological and preclinical studies suggest that males are uniquely vulnerable to prenatal adversity (Clifton, 2010;Davis and Pfaff, 2014). Although studies have revealed sex-specific changes in the developing brain (Bale, 2011;Matthews, 2005, 2008;Kapoor et al, 2009;Weinstock, 2011), the specific mechanisms by which perturbations in the maternal environment promote sex-biased fetal reprogramming remain unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Certainly, one can get to the same destination via different routes. For instance, in neuropsychiatric diseases such as autism, schizophrenia, or depression, although men and women may be given a similar diagnosis, there exist significant sex differences in overall rates, timing of onset, symptom presentation, and treatment efficacy (Heim and Nemeroff, 1999;Heim and Nemeroff, 2001;Sanchez et al, 2001;Goldstein et al, 2002;Heim et al, 2004;Bale, 2006;Brown and Susser, 2008;Bale, 2009;Brown et al, 2009;Heim et al, 2009;Bale et al, 2010;Heim et al, 2010;Brown, 2012;Davis and Pfaff, 2014;Goldstein et al, 2014). Further, mechanistic animal studies modeling endophenotypes of these disorders have demonstrated robust sex differences in the timing of susceptibility to insults to the developing brain where males appear more vulnerable prenatally and females postnatally (Mueller and Bale, 2006;Mueller and Bale, 2007;Ivy et al, 2008;Kapoor et al, 2008;Mueller and Bale, 2008;Kapoor et al, 2009;Ivy et al, 2010;Hsiao and Patterson, 2012).…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%
“…Certainly, numerous neurodevelopmental disorders exhibit strong sex biases, including autism spectrum disorder with an overall sex ratio of 4 : 1 for boys:girls (as reviewed in Newschaffer et al (2007), Davis and Pfaff (2014), and Gore et al (2014)) as well as attention deficit hyperactivity disorder with a male to female sex ratio of 3.2 : 1 (as reviewed in Erskine et al (2013)). The age of onset of these disorders and their male preponderance, suggests that intra-uterine factors are involved in their pathophysiology.…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%
“…Así mismo, la cocaína puede ser un estresor intrauterino que en épocas tempranas del desarrollo altera permanentemente la homeostasis del microambiente neuroendocrino placentario/fetal (Lester & Padbury, 2009), originando una programación perjudicial del sistema de respuesta al estrés, constituido principalmente por el eje Hipotalámi-co-Pituitario-Adrenal (HPA), los glucorticoides y las catecolaminas (Brunton, 2015;Haagen, 2014;Moisiadis & Matthews, 2014); lo que aumenta el riesgo de alteraciones físicas y mentales en el infante con Exposición Prenatal a Cocaína (EPC) (Davis & Pfaff, 2014;Haagen, 2014;Ross, Graham, Money, & Stanwood, 2015).…”
Section: Introductionunclassified
“…La EPC perturba el desarrollo de los procesos biológicos y sumada a un ambiente adverso, tanto intrauterino como posnatal, produce diversas alteraciones en el PSICOLOGÍA http://dx.doi.org/10.21615/cesp.10.1.5 desarrollo físico (Eyler et al, 2009;Lambert & Bauer, 2012;Morrow et al, 2009); cognoscitivo -atención, aprendizaje/memoria, lenguaje- (Henry et al, 2007;Magri et al, 2007;Morrow et al, 2009;Linares et al, 2006), y emocional (Coleman et al, 2014;Davis & Pfaff, 2014;Haagen, 2014;Lucantonio, Stalnaker, Shaham, Niv, & Schoenbaum, 2012;Moisiadis & Matthews, 2014;Richardson, Goldschmidt, Larkby, & Day, 2013), que persisten a lo largo de la vida.…”
Section: Introductionunclassified